2018
DOI: 10.1007/s11356-018-3522-9
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of swale factors implicated in pollutant removal efficiency using a swale database

Abstract: Swales are recognized as traditional basic open-drainage systems which are obviously capable to remove stormwater-borne pollutants. In spite of the numerous case studies on their performances, an overall assessment of swale efficiency to reduce pollutant discharge as well as an evaluation of the factors that could influence it are rare. In order to gain a better understanding of these aspects, a database was designed by collecting performance results and design characteristics from various swales reported in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 76 publications
(115 reference statements)
1
12
0
3
Order By: Relevance
“…Road verges can provide a barrier to soil erosion: one study found that the addition of a 90 cm wide grass strip at the edge of forest roads reduced total sediment loss by an average of 56% (Appelboom, Chescheir, Skaggs, & Hesterberg, ). Many studies demonstrate that roadside vegetation, filter strips and swales (shallow, vegetated channels) provide water filtration, bioremediation and flow regulation (Appendix ), for example reducing water flow by 75%–90% during storm events (Henderson, Smith, & Fitch, ), and swales reducing total suspended soils by 56% and trace metals by 62% (reviewed in Fardel, Peyneau, Béchet, Lakel, & Rodriguez, ).…”
Section: Evidence For Es Provisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Road verges can provide a barrier to soil erosion: one study found that the addition of a 90 cm wide grass strip at the edge of forest roads reduced total sediment loss by an average of 56% (Appelboom, Chescheir, Skaggs, & Hesterberg, ). Many studies demonstrate that roadside vegetation, filter strips and swales (shallow, vegetated channels) provide water filtration, bioremediation and flow regulation (Appendix ), for example reducing water flow by 75%–90% during storm events (Henderson, Smith, & Fitch, ), and swales reducing total suspended soils by 56% and trace metals by 62% (reviewed in Fardel, Peyneau, Béchet, Lakel, & Rodriguez, ).…”
Section: Evidence For Es Provisionmentioning
confidence: 99%
“…Spatial arrangement: Air filtration: affected by proximity of vegetation to the pollution source and other factors; poor design can reduce air quality, for example, trees in street canyons reduce air flow and concentrate pollutants (reviewed in Abhijith et al, 2017;Baldauf, 2017;Janhäll, 2015) Noise reduction: affected by tree density (Ow & Ghosh, 2017) Pollinators: benefit from mosaic management (e.g. Noordijk et al, 2009) and prioritizing habitats a few meters back from the road edge Temperature regulation: affected by vegetation type and configuration (Sodoudi, Zhang, Chi, Müller, & Li, 2018) Water filtration: affected by swale design characteristics (Fardel et al, 2019)…”
Section: Future Developments In Connectivity Provided By Vergesmentioning
confidence: 99%
“…Researchers [46] investigated parameters influencing the reduction of pollutant concentrations from swales. High efficiency ratios were observed for TSS (median 56%) and total trace metals (median ≥ 62%), suggesting that these pollutants are efficiently trapped by sedimentation in swale bed and/or filtered within swale soil.…”
Section: Filter Strips and Vegetated Swalesmentioning
confidence: 99%
“…Il est à noter que les IC 95 % sont d'autant plus forts que les concentrations en polluants sont faibles en entrée de noue ou que les abattements sont faibles. Ce résultat rappelle que les meilleures performances sont souvent caractérisées avec des niveaux de contamination des eaux élevés (Fardel et al, 2019).…”
Section: Evaluation De La Reproductibilité D'indicateurs De Performanunclassified
“…L'aménagement de techniques alternatives (TA) de gestion des eaux pluviales connaît une croissance rapide depuis les années 1990 pour réduire les risques d'inondation et préserver la qualité des écosystèmes (Fletcher et al, 2013). Les noues, des larges fossés souvent végétalisés, font aujourd'hui partie des TA de plus en plus plébiscitées par les aménageurs, notamment pour leurs capacités de traitement des matières en suspension (MES) et des éléments traces métalliques (ETMs) (Fardel et al, 2019). Plusieurs types de noues se sont développés depuis une trentaine d'années, comme les noues de transport pour réguler les débits et les noues de filtration, optimisées pour l'épuration des eaux de ruissellement (Gavrić et al, 2019).…”
Section: Introductionunclassified